Perception and Use of Primary Healthcare Services Among People With Cardiometabolic Diseases in Two Resource-Limited Areas in Nepal: A Mixed Methods Study - Peoples, Nicholas; Gong, Enying; Gautam, Kamal; Khanal, Shree N.; Kohrt, Brandon A.; Koirala, Suraj; Amatya, Archana; Xiong, Shangzhi; Østbye, Truls; Moe, Jeffrey; Long, Qian; Yan, Lijing L. (Frontiers in Public Health, 2021)
Nepal is a country in south Asia with a high burden of cardiometabolic diseases (CMDs). Strengthening primary healthcare (PHC) is a key strategy to mitigate this increasing burden and achieve universal health coverage. While previous studies in Nepal have assessed PHC use among the elderly, none have specifically explored PHC use among people with CMDs. Therefore, this mixed-methods study aimed to assess the use and perception of PHC services in Nepal among people living with CMDs for primary and secondary prevention of cardiovascular disease. We used a quantitative survey followed-up by semi-structured qualitative interviews. The sampling frame comprised five PHC facilities in Sindhuli district (rural; eastern Nepal) and five in Kailali district (urban; western Nepal), with participants selected from each facility via convenience sampling. 114 people (mean age: 54.5 ± 14.7, sex ratio 1.04) with CMDs participated in the survey. Survey data showed general dissatisfaction with PHC services. Medicine cost was rated “too expensive” by 52% and 63% of rural and urban participants, respectively. Interview data showed that perceived poor bedside manner was tied to negative perceptions of PHC quality, and vice versa. Lack of resources and excessive barriers to care was mentioned by every interviewee. In conclusion, PHC use was high but overall satisfaction relatively low. Our results suggest that bedside manner is a practical target for future research. Additionally, we identified several barriers to care, and, based on existing literature, we suggest electronic-health interventions may have potential to mitigate these challenges.